# Streamline question

Let $\textbf{F}:\mathbb{R}^2 \to \mathbb{R}^2$ be a vector field defined as $$\textbf{F}(x,y) = (x^2, y+1)$$ Find the streamline of $\textbf{F}$ that passes through the point $(1,1)$.

Define $$\textbf{r}(t) = (x(t), y(t))$$ then $$\textbf{r}'(t) = (x'(t), y'(t)) = \textbf{F}(x(t),y(t)) = (x^2(t), y(t)+1)$$ so we get two differential equations. Namely $$x'(t) = x^2(t) \mbox{ and } y'(t) = y(t) + 1$$ We beging solving \begin{align} y(t) = e^{t} \int e^{-t} dy = e^{t} (-e^{-t} + C) = e^{t}C - 1 \end{align} and $$\int \frac{\frac{\partial x(t)}{\partial t}}{x^2(t)} = \int 1 \partial t$$ so $$x(t)= -\frac{1}{t + B}$$ Now $$\textbf{r}(0) = (x(0), y(0)) = (-\frac{1}{t + B}, e^{t}C - 1) = (1,1)$$ So $C = 2$ and $B = -1$ and $$\textbf{r}(t) = (x(t), y(t)) = (-\frac{1}{t - 1}, 2e^{t} - 1)$$

Is this correct?

-
In the last step, when $t=0$, you should have $({-1\over 0+B}, e^0C-1)=(1,1)$. So $C=2, B=-1$ and $r(t)=({-1\over t-1}, 2e^t-1)$. – David Mitra Mar 8 '12 at 13:37
Whoops. Thanks! – docjay Mar 8 '12 at 13:38

It looks fine except for the last step where you're solving for the constants. When $t=0$, you should have $${\bf r}(0)=\bigl(\,\textstyle{−1\over 0+B},e^0\cdot C−1\,\bigr)=(1,1)\ \ \Rightarrow \ \ B=−1,\ C=2 \ \ \Rightarrow\ \ {\bf r}(t)=\bigl(\,{-1\over t-1},2e^t−1\,\bigr).$$
And on a picky note, at the outset, you should define ${\bf r}(t)=\bigl(x(t),y(t)\bigr)$, ${\bf r}(0)=(1,1)$.